Comprehensive analysis of the prognostic value of the chemokine-like factor-like MARVEL transmembrane domain-containing family in gastric cancer - Liang, Zhikun (J Gastrointest Oncol, 2021)
BACKGROUND: The chemokine-like factor (CKLF)-like MARVEL transmembrane domain-containing (CMTM) family refers to a family of transcriptional repressor genes. CMTMs are closely associated with the epigenetic regulatory mechanisms and development of multiple malignancies, including gastric cancer. However, their specific biological functions and prognostic values in gastric cancer have yet to be elucidated. METHODS: Tumor sample datasets were retrieved and analyzed using databases including Oncomine, STRING, GEPIA2, cBioportal, and Kaplan-Meier plotter. To investigate the prognostic role of CMTMs in gastric cancer, we applied unsupervised hierarchical clustering analysis of CMTM gene expression patterns. RESULTS: While the mRNA levels of CMTM1/3/6/7/8 were upregulated in gastric cancer, CMTM2/4/5 showed no statistically significant difference at the mRNA level in patients with gastric cancer. Moreover, the mRNA expressions of different CMTMs exhibited strong correlations with various clinical parameters of patients with gastric cancer, including tumor stage, metastatic lymph node status, H. pylori status, and tumor grade. Also, the results suggested that elevated levels of CMTM3/5 mRNA had a significant association (P<0.05) with poor overall survival, progression-free survival, and post-progression survival. Conversely, elevated expression of CMTM2/4/6 mRNA had a significant association with better overall survival, progression-free survival, and post-progression survival. Unsupervised hierarchical clustering analysis successfully identified 2 major clusters of patients as follows: signature #1: CMTM4/6/8 and signature #2: CMTM1/2/3/5/7. Signature #2 was closely correlated with poorer overall survival, which indicated that the expression pattern of the CMTM family could be a novel prognostic factor for patients with gastric cancer. CONCLUSIONS: These results suggest that the expression levels of CMTM genes possibly have prognostic value as a biomarker of gastric cancer.